PENGARUH PENGGUNAAN MEDIA SCRAPBOOK TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA DI SANGGAR BELAJAR KEPONG MALAYSIA - Alia Nurjannah; Dewi Kesuma Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using Scrappbook learning media on the critical thinking skills of fourth-grade elementary school students at Sanggar Belajar Kepong Malaysia in the subject of the five senses. This study used a pre- experimental design with a one-group pretest-posttest design. The sampling technique was total sampling, resulting in a sample of six students. Data collection was conducted by administering a critical thinking skills test in the form of an essay. The data analysis technique used was the paired sample t-test. The results showed that the calculated t-value (10.764) > t-table (2.570) and the significance value 0.001 < 0.05, which means that there is an effect of using Scrappbook learning media on the critical thinking skills of fourth-grade elementary school students at Sanggar Belajar Kepong Malaysia. The effect was also demonstrated by the posttest scores being higher than the pretest scores, namely 93,16 > 52.